Salicylic acid: its properties and role in stimulating the defense system in plants against fungal pathogens - Qusai Hattab Madhi / Talal Hussein Saleh / Ghassan Mahdi Dagher ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2022)
Increasing demand for global food production in the agricultural sector is a critical driving force for the development of new disease management methods that are effective against known pathogens. Plants possess specialized structures, chemicals, and complex mechanisms to defend themselves against pathogens, and understanding these defense mechanisms and pathways is critical. To develop innovative approaches to protecting crop plants from disease as pathogens are constantly developing sophisticated means to penetrate plant defenses. Plant defense pathways include a number of signaling compounds that regulate the production of defense-related chemicals. These pathways are strongly associated with salicylic acid (SA). Salicylic acid plays an important role in stimulating plant defense against a variety of fungal pathogens and abiotic stresses through morphological, physiological and biochemical mechanisms. DOI /10.54633/2333-021-042-001